Music and school, a late confluence in contemporary Spain: the LGE as a turning point - Gelabert Gual, Llorenç; Motilla Salas, Xavier (Historia y Memoria de la Educación, 2024)
The teaching of music at school has expanded throughout the different educational legislative contexts that Spain has lived through in recent times. While the confluence of art and education constitutes a normalized and generalized practice in current school spaces, the historical deficit of schools without art continued until the last quarter of the last century. The General Law of Education (LGE) of 1970 established for the first time, at the curricular level, a space dedicated to artistic education, which included musical education, plastic expression and dramatization, with ambitious contents and methodological proposals as well as avant-garde references. This milestone was preceded by more than a century of sociopolitical and legislative vicissitudes that conditioned education in general and the role that music should assume in compulsory education in particular. Through this contribution we analyze the presence of music in the school through the different legislative contexts of the Spanish State, from the first references to the arts in the Law of Public Instruction of 1857 to the supposed consolidation of music in schools, at least legislatively, in the last third of the 20th century with the turning point represented by the LGE.